PROPOSAL OF A GOVERNANCE MODEL FOR RESEARCH CENTERS BASED ON STRUCTURE UNIVERSITY-COMPANY - Monteiro, Letícia Orselli [UNESP]; Montoro, Stela Basso [UNESP]; Santos, David Ferreira Lopes [UNESP] (Curran Associates, 2021)
The importance of organizations originated through Science, Technology and Innovation programs in countries and regions, such as the Research and Development Centers have received increasing attention in the literature. However, there is a theoretical-empirical gap regarding the management models that can be implemented in the administration of these Research and Development Centers, especially in models that bear the assumptions of governance, environment and social in their design. Thus, the objective in this study was to propose a governance structure for Research and Development Centers for innovation and technology in the public-private relationship. A case study was used as a strategy, directed to the Engineering Research Center - Plant Health in Sugarcane of the School of Agrarian and Veterinarian Sciences at São Paulo State University, with the use of research- action like method. This technique, in line with management theories and models, business practices and sustainability criteria “Environmental, Social and Governance” supported the formulation of a governance model capable of contemplating the complexity of the Engineering Research Center investigated as an articulating organization in the university-company relationship.
Keywords: ESG sustainability; Innovation; Performance; R&D centers